Self-Balance of Intestinal Flora in Spouses of Patients With Rheumatoid Arthritis - Liu, Zhihui; Wu, Yuxi; Luo, Yubin; Wei, Shixiong; Lu, Chenyang; Zhou, Yi; Wang, Jing; Miao, Ting; Lin, Hui; Zhao, Yi; Liu, Qi; Liu, Yi (Frontiers in Medicine, 2020)
We sought to characterize and assess differences in compositions of intestinal flora between patients with rheumatoid arthritis (RA) and their respective spouses. 80 volunteers were recruited, including 30 pairs of RA patients and their spouses, and 20 healthy individuals. Fresh stool samples were collected, processed, and 16S rRNA-sequencing was performed. Data were analysed using an operational taxonomic units-based method, and community structure assessments were performed. Community composition analysis indicated that there were similar intestinal microbiota structures in RA and in their respective spouses. Gut microbiota in spouses of RA were different from those of the healthy controls group, but these differences were not significant. We found that Blautia spp. and Streptococcus spp. were two most associated species in RA and these taxa were significantly higher in comparison to healthy controls. In contrast, our findings suggested that Roseburia spp. and Lachnoclostridium spp. were significantly lower in the RA in comparison to healthy controls. In conclusion, RA patients shared similar gut microbiota pattern with their spouses which were different from healthy individuals.The findings suggest that disturbance of the balance of gut microbiota may play an important role in the dynamics of pathogenesis of RA.